2016
DOI: 10.1007/s10803-016-2954-7
|View full text |Cite
|
Sign up to set email alerts
|

Continuity and Change in Cognition and Autism Severity from Toddlerhood to School Age

Abstract: Diagnoses at 24-months, appear to be reliable and stable. Further research is needed to investigate whether early identification, which provides more opportunity to access early intervention, may in turn facilitate cognitive development over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 41 publications
1
33
0
1
Order By: Relevance
“…The Mullen NVIQ and VIQ scores were used with the WASI Perceptual Reasoning Index (PRI) and Verbal Comprehension Index (VCI) quotients (mean 100; SD 15) in the analysis of, respectively, non-verbal and verbal skills. The MSEL and WASI are not equivalent but both provide a measure of verbal, non-verbal and overall cognitive functioning and have been used to assess change in cognitive skills in children with ASD from toddlerhood to mid-childhood (Clark et al 2017 ). In this sample the correlation between the Mullen ELC at 36 months and the WASI FSIQ at 84 months was moderate across groups (Pearson’s R = .424, p < .001).…”
Section: Methodsmentioning
confidence: 99%
“…The Mullen NVIQ and VIQ scores were used with the WASI Perceptual Reasoning Index (PRI) and Verbal Comprehension Index (VCI) quotients (mean 100; SD 15) in the analysis of, respectively, non-verbal and verbal skills. The MSEL and WASI are not equivalent but both provide a measure of verbal, non-verbal and overall cognitive functioning and have been used to assess change in cognitive skills in children with ASD from toddlerhood to mid-childhood (Clark et al 2017 ). In this sample the correlation between the Mullen ELC at 36 months and the WASI FSIQ at 84 months was moderate across groups (Pearson’s R = .424, p < .001).…”
Section: Methodsmentioning
confidence: 99%
“…Barbaro and Dissanayake () have also shown that the following behavioral markers at 24 months contribute to a shift to a diagnosis other than ASD by 48 months: Better eye contact, more directed vocalizations, integration of gaze, and directed vocalizations or gestures as well as a higher nonverbal developmental quotient. Clark et al () have suggested that a diagnosis of ASD at 24 months appears to be reliable and stable from toddlerhood to school age. Therefore, these features might be very informative for routine surveys.…”
Section: Discussionmentioning
confidence: 99%
“…We cannot claim that these changes are significant, different test methods had been used at T2 and T3. However, the tools are designed to measure the same construct 28 and results illustrate the varying cognitive/developmental trajectories in children with BIF. Our cognitive results, although not statistically substantiated, support the instability of an IQ in the BIF area 11 and the need of follow-up assessments of cognitive functions.…”
Section: Discussionmentioning
confidence: 99%